Policy on reintegration of women with histories of substance abuse: A mixed methods study of predictors of relapse and facilitators of recovery - VanDeMark Nancy R (BMC, 2007)
Abstract Background The predominant U.S. policy approach toward individuals with substance abuse problems has relied on stigma and punishment by withholding access to education, cash assistance, housing, social support, and normal social roles. In contrast to this approach, the theory of reintegrative shaming asserts that providing individuals with the opportunity to reconnect with society is more effective in reducing potential to relapse to crime and drug abuse. Strategies that promote such reconnection include expanding access to basic needs and supportive relationships along with increasing opportunities to fully participate in mainstream social roles. Methods The present cross-sectional study examined the predictors of relapse and the facilitators of recovery in a sample of 325 women with histories of substance abuse. Analysis of secondary data, collected as part of a national cross-site study, employed a mixed methods approach conducting (1) logistic regression to examine the predictors of relapse and (2) an inductive qualitative analysis of responses from open-ended items to explore the women's perceptions of barriers to and facilitators of recovery. Results Results suggest that lower levels of instrumental support, affective support, and participation in normal roles (such as parent, employee, student, and citizen) are significant predictors of relapse to drug use and criminal behaviors. Qualitative findings support the quantitative results, revealing that participating women perceived the variables of support and role participation as critical in facilitating their recovery. They also noted the importance of individual characteristics such as optimism and strength and emphasized the significance of their relationship with their children in motivating them to avoid relapse. Findings suggest that punitive policies toward women with substance abuse histories may be ineffective. Conclusion The author concludes that current policies designed to withhold access to basic needs such as housing, education, cash assistance, and positive relationships may deprive women with histories of substance abuse of the means to reconnect with society. Policies that promote access to basic needs and offer avenues for women to participate in normal societal roles should be more fully explored.